2007
DOI: 10.2165/00126839-200708040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Cardiac Safety Assessment??of Drugs

Abstract: The heart is a frequent site of toxicity of pharmaceutical compounds in humans, and when developing a new drug it is critical to conduct a thorough preclinical evaluation of its possible adverse effects on cardiac structure and function. Changes in cardiac morphology such as myocardial necrosis, hypertrophy or valvulopathy are assessed in regulatory toxicity studies in laboratory animals, although specific models may be needed for a more accurate detection of the risk. The potential proarrhythmic risk of new d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 106 publications
0
20
0
1
Order By: Relevance
“…While a number of the withdrawn drugs had been shown to directly interfere with the hERG channel, it has been since shown that multiple ionic currents can influence hERG current block and furthermore hERG block alone sometimes does not provide a meaningful indication of QT prolongation or for that matter TdP. Furthermore, measurement of QT prolongation itself was shown to be highly sensitive for TdP, but not specific Hanton, 2007;Hoffmann & Warner, 2006). The emphasis on hERG in the non-clinical part of the guideline has had the unintended effect of substantially increasing the attrition rate of potentially promising compounds in development.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of the withdrawn drugs had been shown to directly interfere with the hERG channel, it has been since shown that multiple ionic currents can influence hERG current block and furthermore hERG block alone sometimes does not provide a meaningful indication of QT prolongation or for that matter TdP. Furthermore, measurement of QT prolongation itself was shown to be highly sensitive for TdP, but not specific Hanton, 2007;Hoffmann & Warner, 2006). The emphasis on hERG in the non-clinical part of the guideline has had the unintended effect of substantially increasing the attrition rate of potentially promising compounds in development.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug effects on cardiac electrophysiological function, in particular impulse formation and conduction, are usually evaluated through changes in ECG, generally recorded in dogs, pigs or monkeys. TdP-related arrhythmias are detected very seldom in healthy dogs or monkeys but the triggering of arrhythmia could be investigated for example under hypokalemic conditions with artificially created bradycardia [4]. Adverse drug effects on cardiac electrophysiological function, in particular impulse formation and conduction, are usually evaluated through changes in ECG, generally recorded in dogs, pigs or monkeys.…”
Section: Cardiosafety Assessment Of Preclinical Positive Signalsmentioning
confidence: 99%
“…Although the hERG channel has been shown to be the most significant of the risk factors that cause LQT, the full mechanism of TdP arrhythmia is more complex [13,15] and the range of relevant biological targets linked with other cardiac toxicities is much broader [4]. Other ion channels involved in regulating cardiac action potential are also known to cause cardiotoxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate this problem, ADRs caused by a single candidate drug are closely monitored and investigated during the drug development and approval process [2]. For instance, drug candidates are routinely tested in many in vitro and in vivo assays to predict their toxicity to humans [3]. Similarly, subsequent clinical trials usually focus on a single drug and its therapeutic effect against a particular disease or condition.…”
Section: Introductionmentioning
confidence: 99%